2008
DOI: 10.1080/00048670802512107
|View full text |Cite
|
Sign up to set email alerts
|

Shyness 3: Randomized Controlled Trial of Guided Versus Unguided Internet-Based CBT for Social Phobia

Abstract: The reliability of this Internet-based treatment programme for social phobia has been confirmed. The therapist-guided condition was superior to the self-guided condition, but a subgroup of participants still benefited considerably from the latter. These data confirm that self-guided education or treatment programmes for common anxiety disorders can result in significant improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(151 citation statements)
references
References 35 publications
9
136
3
3
Order By: Relevance
“…First, the homogeneity of our sample (all patients had SAD as a main diagnosis) and of the intervention (manualized CBGT, semi-standardized e-mails) are strengths of the study. Further, although the effectiveness of internet-based cognitive-behavior therapy has been shown for the treatment of several psychiatric conditions including SAD (Berger et al, 2011;Hedman et al, 2011;Gadit, 2006;Tilfors et al, 2008;Titov et al, 2008) and previous studies have confirmed the effectiveness of motivational e-mail support as an adjunct to internetdelivered self-help (e.g. Lancee et al, 2013), this is the first study systematically testing the effect of e-mail support as an adjunct to face-to-face group therapy.…”
Section: Discussionmentioning
confidence: 99%
“…First, the homogeneity of our sample (all patients had SAD as a main diagnosis) and of the intervention (manualized CBGT, semi-standardized e-mails) are strengths of the study. Further, although the effectiveness of internet-based cognitive-behavior therapy has been shown for the treatment of several psychiatric conditions including SAD (Berger et al, 2011;Hedman et al, 2011;Gadit, 2006;Tilfors et al, 2008;Titov et al, 2008) and previous studies have confirmed the effectiveness of motivational e-mail support as an adjunct to internetdelivered self-help (e.g. Lancee et al, 2013), this is the first study systematically testing the effect of e-mail support as an adjunct to face-to-face group therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos controlados avaliados apontam para a eficácia das intervenções cognitivas e comportamentais (tais como EXP e TTC), sozinhas ou associadas a outras técni-cas (relaxamento e treino em respiração), na redução dos sintomas do TAS [17][18][19] quando comparadas a outros tipos de abordagens psicoterápicas ou a grupo controle [21][22][23][24][25][26][28][29][30][31][32][33][34]41,43 . Tais achados são confi rmados por Acarturk et al 52 em estudo meta-analítico recente que afi rmou também que essa efi cácia tende a se manter e, em alguns casos, até melhorar nas medidas de follow-up.…”
Section: Discussionunclassified
“…As novas formas de apresentação da TCC, como a autoterapia através de um livro-guia 31 , a terapia via internet [24][25][26][28][29][30] Tratamento cognitivo e/ou comportamental e transtorno de ansiedade social -MULULO ET AL.…”
Section: Discussionunclassified
“…Prior to developing TD iPT, we developed and evaluated disorder-specifi c iPT interventions to treat social phobia Titov, Andrews, Choi, Schwencke, & Mahoney, 2008;Titov, Andrews, Schwencke, et al, 2010;, PD (Wims et al, 2010), GAD , and depression (Perini et al, 2009;Titov, Andrews, Davies, et al, 2010). These interventions were evaluated in 12 RCTs and 3 open trials with participants who met a principal DSM-IV diagnosis for the relevant disorder.…”
Section: Results Of Our Trials Of Disorder-specifi C Iptmentioning
confidence: 99%